De novo high-accuracy transcriptomes from long-read sequencing reveals a wide variety of novel splice variants in copepodids and adult female salmon lice (Lepeophtheirus salmonis) - Hansen, Sine Alise Hartvigsen; Ramberg, Sigmund; Lekanova, Nadezhda; Høyheim, Bjørn; Horsberg, Tor Einar; Andreassen, Rune; Bakke, Marit Jørgensen (Frontiers in Marine Science, 2023)
Former transcriptome studies of the ectoparasitic salmon louse (Lepeophtheirus salmonis) are based on short-read sequencing and in silico predictions, with the disadvantage of inadequately describing splice variants and insufficient differentiation between duplicated genes. In the present study, a de novo full-length transcriptome (TSA accession GKKU00000000) was generated using single-molecule long-read RNA-sequencing (PacBio IsoSeq platform) corrected by short reads (Illumina platform) from the same RNA samples. The two samples, cephalothorax of an adult female and her copepodid offspring, were analyzed separately to facilitate comparison and identification of transcripts unique to each life stage. Each transcript has been supported by two or more full-length non-chimeric reads and at least three short reads, ensuring high-sequence accuracy. A total of 31,092 unique high-accuracy full-length transcripts with an open reading frame > 150 bp, originating from 10,034 unique loci of the salmon louse genome, were identified. More than half of the transcripts are life-stage specific, exclusively present in either the copepodid or adult sample. Approximately one-third of the transcripts were full splice matches with predicted protein coding transcripts presented in NCBI, thus validating these. More than half of the transcripts constituted novel isoforms with at least one new splicing site. We conclude that the full-length transcriptomes represent a versatile reference resource of transcripts. Suitable applications include expression studies, SNP mining, and studies on the biological effects of differences in gene (or isoform) expression between copepodids and adult females. The additional functional annotation of 88% of transcripts allows for identification of gene families of particular interest and for exploration of gene networks and enrichment analysis following expression studies.